A study for establishing E-commerce Business Satisfaction model to measure e-commerce success in SMEs. (15th April 2008) - Gide, E.; Wu, M.X.
For the last ten years, while many e-commerce systems have been successfully adopted in businesses across different industries, a significant numbers have failed, especially in Small to Medium Enterprises (SMEs). To date, no detailed academic or industry studies have been found in the field of business satisfaction with e-commerce systems. This research aims to develop an effective measure of e-commerce success from a business point of view, termed E commerce Business Satisfaction (EBS). This paper also describes the existing knowledge on satisfaction with e-commerce systems, and provides a research model for analysing EBS based on Gide and Wu's proposed EBS model.